Oclusión baja en el recién nacido - Lizaso, Isabel; Xavier, Artigas; Benedictti, Luis; Wettstein, Juana; Sbárbaro, Orestes; Maizonave, Berta; Puigdevall, Juan (Cirugía del Uruguay, 1990)
We wish to point out that the authorities of this XXXIX Uruguayan Congress of Surgery have given greater participation in the same to surgery pediatric, evidencing a laudable concern for the same and personally we appreciate that They will entrust us with the realization of this Table.